2016
DOI: 10.1002/med.21417
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerases: Resistance versus Sensitivity, How Far We Can Go?

Abstract: DNA topoisomerases are ubiquitously present remarkable molecular machines that help in altering topology of DNA in living cells. The crucial role played by these nucleases during DNA replication, transcription, and recombination vis-à-vis less sequence similarity among different species makes topoisomerases unique and attractive targets for different anticancer and antibacterial drugs. However, druggability of topoisomerases by the existing class of molecules is increasingly becoming questationable due to resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 210 publications
(242 reference statements)
0
19
0
1
Order By: Relevance
“…Examples of enzymes belonging to the Top IA subfamily are bacterial topoisomerase I, bacterial topoisomerase III, eukaryotic topoisomerase III and reverse gyrase 1,6,20 .…”
Section: Type Ia Topoisomerasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of enzymes belonging to the Top IA subfamily are bacterial topoisomerase I, bacterial topoisomerase III, eukaryotic topoisomerase III and reverse gyrase 1,6,20 .…”
Section: Type Ia Topoisomerasesmentioning
confidence: 99%
“…The most important example of a type IB topoisomerases is the eukaryotic Top I (including human Top I), which is an important molecular target of anticancer therapies. In addition, Top IB group includes poxvirus topoisomerase and eubacterial Top IB 6,9 .…”
Section: Type Ib Topoisomerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was subjected to electrophoresis in 0.8% agarose gel and stained with ethidium bromide. cells targeted with TOP poisons (Bansal et al, 2017;Ganapathi and Ganapathi, 2013). In this context, our current study uncovered that HMGA2 is a crucial factor that can affect TOP2A function.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, several tumor‐associated proteins such as YB‐1 (Wu et al , ), p53 (Gobert et al , ) (Kwon et al , ) and ARF (Karayan et al , ) have been shown to enhance TOP activity either through direct protein–protein interactions or by enhancing TOP2 ATPase activity. Such findings could aid in our understanding of cellular chemoresistance that is often observed in cancer cells targeted with TOP poisons (Bansal et al , ; Ganapathi and Ganapathi, ). In this context, our current study uncovered that HMGA2 is a crucial factor that can affect TOP2A function.…”
Section: Discussionmentioning
confidence: 90%